(untitled) (Journal of Misan Researches, 2024)
The Neolithic is considered an important stage in human life, in which he learned agriculture, animal domestication, and stability, which had a great impact in creating spiritual, sensory images, which brought him to a stage of contemplation and innate belief in certain beliefs, especially in the beginnings of the Neolithic, which helped him communicate with What surrounds him, from a cosmic, environmental and social environment, with innate answers to questions and fears that occupied his mind, so that these innate beliefs become a primitive stage for the tendency of faith, sanctification and worship, in the advanced civilizational periods of human life.